Short- and long-read metagenomics of urban and rural South African gut microbiomes reveal a transitional composition and undescribed taxa - Fiona B Tamburini; Dylan Maghini; Ovokeraye H Oduaran; Ryan Brewster; Michaella R Hulley; Venesa Sahibdeen; Shane A Norris; Stephen Tollman; Kathleen Kahn; Ryan G Wagner; Alisha N Wade; Floidy Wafawanaka; et al. (My University, 2022)
Human gut microbiome research focuses on populations living in high-income countries and to a lesser extent, non-urban agriculturalist and hunter-gatherer societies. The scarcity of research between these extremes limits our understanding of how the gut microbiota relates to health and disease in the majority of the world's population. Here, we evaluate gut microbiome composition in transitioning South African populations using short- and long-read sequencing. We analyze stool from adult females living in rural Bushbuckridge (n = 118) or urban Soweto (n = 51) and find that these microbiomes are taxonomically intermediate between those of individuals living in high-income countries and traditional communities. We demonstrate that reference collections are incomplete for characterizing microbiomes of individuals living outside high-income countries, yielding artificially low beta diversity measurements, and generate complete genomes of undescribed taxa, including Treponema, Lentisphaerae, and Succinatimonas. Our results suggest that the gut microbiome of South Africans does not conform to a simple "western-nonwestern" axis and contains undescribed microbial diversity.